The Effect of Addition of Avocado Fruit Seeds On Bioplastic Biodegradation - Fathurohman, Viki; Alisaputra, Darmawan; Sedyadi, Endaruji (Proceeding International Conference on Science and Engineering, 2020)
Bioplastics can be made with chitosan as a base material with a sorbitol plasticizer and avocado-based seed starch. This study tries to discuss the comparison of avocado seeds to bioplastic biodegradability required based on weight loss in soil media. This research was carried out in empathic, namely making avocado starch, making bioplastics, analyzing bioplastic functional groups, and testing biodegradation of bioplastics in soil media. Variations used are avocado seeds used are 0; 0.1; 0.3; 0.5; 0.7; and 1.4 grams. Bioplastic functional group analysis was performed using FTIR. Bioplastic biodegradability in soil media. Bioplastics are 76% degraded within 12 days in the soil. This shows that bioplastics can be biodegradable.